Management of green mold in postharvest citrus with seaweed extract (Research, Society and Development, 2021)
This study aimed to evaluate the effectiveness of different dosages of a product based on seaweed extract from Ascophyllum nodosum in the management of green mold in citrus postharvest. Dosages of 0; 25; 50; 75 and 100 mL L-1 were used of the commercial product based on seaweed extract and, as a comparison, a systemic fungicide from the benzimidazole group was used. In vitro experiments were carried out to check the effect of the product and its possible mechanisms of action, the following parameters being evaluated: mycelial growth, sporulation, electrolytes leakage and fungicidal and/or fungistatic activity. Then, an in vivo experiment was carried out in order to assess the incidence and severity of green mold in 'Valencia' orange fruits. It was observed that the dosages of 75 and 100 mL L-1 were the most effective in reducing mycelial growth and the production of conidia of the pathogen, with a fungistatic effect of the product based on the seaweed extract. It was found that the product modify the plasma membrane permeability of the fungus at the dosage of 100 mL L-1, which may be a possible mechanism of action on the pathogen. In addition to being able to reduce the incidence and severity of green mold in postharvest on orange fruits at dosage of 75 mL L-1. Thus, it is concluded that the product based on the A. nodosum seaweed extract can be included in the integrated management of diseases in postharvest of citrus.